Environmental balance of shipping emissions reduction strategies - Zis, Thalis; North, Robin; Angeloudis, Panagiotis; Ochieng, Washington Yotto; Bell, Michael G. H. (My University, 2014)
Maritime shipping is regarded as the most efficient mode of transport; however, its contribution to climate change through greenhouse gas emissions and the health issues related to shipping activity near residential centers cannot be neglected. In recent years, the efforts of regulators, ship operators, and port authorities have led to actions for ship emissions reduction to improve shipping’s environmental performance. This work builds on an activity-based methodology that allows the estimation of emissions and examines environmental effects of slow steaming, fuel regulations, near-port speed-reduction schemes, and cold ironing. Pollutant emissions of carbon dioxide, sulfur dioxide, nitrogen oxides, and black carbon are modeled. A linear programming model minimizes fuel consumption through speed differentiation on a shipping line’s routes based on fuel costs and binding regulations in each segment of the journey. Although the examined emissions-reduction actions may have a positive regional environmental effect by cutting emissions, it is possible that additional emissions are generated elsewhere because of increased sailing speeds beyond regulated areas. Trade-offs between pollutants are observed for reduction actions that may have a positive effect on some emission species but at the same time result in additional particulate matter and black carbon emissions. The presented framework allows key actors to conduct comprehensive studies and design improved emissions reduction actions with fewer negative impacts in other areas.